Governance in the Digital Age: Grassroots Initiatives and Urban Commercial Vitality - Xu, Bo (Journal of Global Economy, Business and Finance, 2026)
Under the new development paradigm, grassroots digital governance has emerged as a pivotal direction for urban modernization, offering a robust mechanism to stimulate commercial vitality. This study constructs a fixed-effects model by integrating panel data from Chinese prefecture-level cities with micro-survey data on grassroots digital governance, empirically examining its impact on urban commercial vitality. Results reveal a significant positive effect that persists across multiple robustness tests. Mechanism analysis identifies business environment optimization and entrepreneurial activity enhancement as the primary pathways through which grassroots digital governance stimulates commercial vitality. Consequently, the study recommends strengthening digital technology promotion in grassroots governance, fostering a favorable business environment, and encouraging urban innovation and entrepreneurship to enhance commercial vitality.